Antithrombotic therapy and platelet transfusions in hematologic malignancy patients presenting chemotherapy‐induced thrombocytopenia: a French survey. Issue 7 (25th April 2017) - Chalayer, Emilie; Cavalieri, Doriane; Martignoles, Jean Alain; Genthon, Alexis; Tavernier, Emmanuelle; Tardy, Bernard
Abstract : BACKGROUND: Patients with hematologic malignancies are at high risk for both thrombosis and bleeding. During the prolonged periods of thrombocytopenia experienced by patients who are receiving intensive chemotherapy, clinicians often hesitate to prescribe any protection against thrombosis. In case of anticoagulant prescription, it is the prescribers' responsibility to weigh risks and benefits for each patient. Current guidelines exist but do not take into account types of thrombosis, patients' comorbidities, or previous bleeding events. STUDY DESIGN AND METHODS: We proposed to gain insight into hematologists' beliefs about antithrombotic prescription in hematologic malignancy patients, to design future clinical trials. Therefore, we conducted a survey in France to evaluate the practices among a panel of hematologists. RESULTS: We found that more than 92% of the respondents prescribed therapeutic anticoagulation in case of pulmonary embolism or deep venous thrombosis. In the case of therapeutic anticoagulation, only 64% of the physicians reconsidered treatment under a platelet threshold of 50 × 10 9 /L. None of the respondents decided to renounce treatment, nor to discontinue it because of thrombocytopenia, except in distal venous thrombosis or superficial vein thrombosis. One‐fifth of clinicians proposed the insertion of a vena cava filter. CONCLUSION: As observed in the United States and Canada, we noticed discrepancies between recommendations and current practices in France. This highlights the urgent need to conduct studies to evaluate both efficacy and safety of antithrombotics in patients with hematologic cancer and thrombocytopenia.